2012
DOI: 10.1371/journal.pone.0032232
|View full text |Cite
|
Sign up to set email alerts
|

The Mucin MUC4 and Its Membrane Partner ErbB2 Regulate Biological Properties of Human CAPAN-2 Pancreatic Cancer Cells via Different Signalling Pathways

Abstract: The mucin MUC4 and its membrane partner the ErbB2 oncogenic receptor are potential interacting partners in human pancreatic tumour development. However, the way they function is still largely unknown. In this work, we aimed to identify the cellular mechanisms and the intracellular signalling pathways under the control of both ErbB2 and MUC4 in a human pancreatic adenocarcinomatous cell line. Using co-immunoprecipitation and GST pull-down, we show that MUC4 and ErbB2 interact in the human pancreatic adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 49 publications
6
82
1
Order By: Relevance
“…33 Interestingly, transmembrane mucins are characterized by the presence of multiple structural motifs with sequence homology to EGF (referred to as EGF-like), which are thought to mediate heterodimerization of mucins with ERBB receptors (Box 1). 5,34,35 The affinities and functional relevance of these interactions for altered oncogenic signalling are being explored.…”
Section: Mucins In Pancreatic Cancermentioning
confidence: 99%
“…33 Interestingly, transmembrane mucins are characterized by the presence of multiple structural motifs with sequence homology to EGF (referred to as EGF-like), which are thought to mediate heterodimerization of mucins with ERBB receptors (Box 1). 5,34,35 The affinities and functional relevance of these interactions for altered oncogenic signalling are being explored.…”
Section: Mucins In Pancreatic Cancermentioning
confidence: 99%
“…Total proteins were extracted, electro-transferred, immunostained, and visualized as described before [5,23,26,28,29]. Antibodies used are MUC1 (M8, 1/250, from Pr D. Swallow); β-actin (A5441 AC15, 1/5000) from Sigma-Aldrich; cyclin D1 (sc-718, 1/250)and CDK6 (sc-177, 1/ 250) from Santa Cruz; EGFR (#4267s, 1/500), Bcl-2 (#2872, 1/250), phospho P53 (#9284, 1/500), P53 (#9282, 1/500), phospho p42-44 MAPK (#9101, 1/500), p42-44 MAPK (#9102, 1/500), phospho Stat3 (#9145, 1/250), Stat3 (#9139, 1/500), β-catenin (#8480s, 1/1000), phospho AKT (#4060, 1/500), and AKT (#4691s, 1/500) from Cell Signaling, Ozyme.…”
Section: Protein Extraction and Western-blot Analysismentioning
confidence: 99%
“…Carraway et al demonstrated that of the two EGF-like domains present in rat Muc4/Asgp2/Sialomucin complex, interaction with ErbB2 was mediated by EGF1 domain [38]. Human MUC4 contains three EGF domains, and a glutathione S-transferase (GST) fusion construct containing EGF3–EGF1–EGF2 domains of MUC4 forms a stable heterodimer with HER2, while in the HER2 knockdown cells MUC4 can interact with HER3 [39,40]. These interactions subsequently activate various signaling cascades including MAPK, JNK, and STAT-1 that promote cell proliferation and migration in vitro and enhance tumorigenicity and metastasis in vivo (Figure 2) [8,9,12,18,39,40].…”
Section: Role Of Muc4 In the Pathobiology Of Pdacmentioning
confidence: 99%
“…Human MUC4 contains three EGF domains, and a glutathione S-transferase (GST) fusion construct containing EGF3–EGF1–EGF2 domains of MUC4 forms a stable heterodimer with HER2, while in the HER2 knockdown cells MUC4 can interact with HER3 [39,40]. These interactions subsequently activate various signaling cascades including MAPK, JNK, and STAT-1 that promote cell proliferation and migration in vitro and enhance tumorigenicity and metastasis in vivo (Figure 2) [8,9,12,18,39,40]. Additionally, MUC4 can modulate E-cadherin and N-cadherin signaling to promote contact-independent proliferation and drive epithelial-to-mesenchymal transition [9,41].…”
Section: Role Of Muc4 In the Pathobiology Of Pdacmentioning
confidence: 99%
See 1 more Smart Citation